A drug discovery platform: A simplified immunoassay for analyzing HIV protease activity - Kuntida Kitidee (2018)
Although numerous methods for the determination of HIV protease (HIV-PR) activity have been described, new high-throughput assays are required for clinical and pharmaceutical applications due to the occurrence of resistant strains. In this study, a simple enzymatic immunoassay to identify HIV-PR activity was developed based on a Ni2+-immobilized His6-Matrix-Capsid substrate (H6MA-CA) is cleaved by HIV protease-His6(HIV-PRH6) which removes the CA domain and exposes the free C terminus of MA. Following this cleavage, two monoclonal antibodies specific for either the free C-terminal MA or CA epitope are used to quantify the proteolytic activity using a standard ELISA-based system. Specificity for detection of the HIV-PRH6activity was confirmed with addition of protease inhibitor (PI), lopinavir. In addition, the assay was able to detect an HIV-PR variant activity indicating that this assay is capable of assessing viral mutation affect HIV-PR activity. The efficacy of commercially available PIs and their 50% inhibitory concentration (IC50) were determined. This assay provides a high-throughput method for both validating the efficiency of new drugs in vitro and facilitating the discovery of new PIs. In addition, it could serve as a method for examining the influence of various mutations in HIV-PRs isolated from drug-resistant strains. © 2012 Elsevier B.V.